Genome editing with CRISPR-Cas nucleases, base editors, transposases and prime editors - Anzalone, Andrew V; Koblan, Luke W; Liu, David R (Nature biotechnology, 2020)
The development of new CRISPR-Cas genome editing tools continues to drive major advances in the life sciences. Four classes of CRISPR-Cas-derived genome editing agents-nucleases, base editors, transposases/recombinases and prime editors-are currently available for modifying genomes in experimental systems. Some of these agents have also moved rapidly into the clinic. Each tool comes with its own capabilities and limitations, and major efforts have broadened their editing capabilities, expanded their targeting scope and improved editing specificity. We analyze key considerations when choosing genome editing agents and identify opportunities for future improvements and applications in basic research and therapeutics.